Treatment of heparin-induced thrombocytopenia with fondaparinux - Harenberg, Job; Jörg, Ingrid; Fenyvesi, Tivadar (Haematologica, 2004)
Anticoagulation of patients with heparin-induced thrombocytopenia (HIT) may be limited by cross-reaction of HIT antibodies with danaparoid and generation of antibodies during therapy with lepirudin. We used fondaparinux to treat 6 patients with a history of HIT with thromboembolism and 2 patients with thrombocytopenia during low-molecular-weight heparin administration.
Gesehen am 21.04.2022